2018
DOI: 10.1097/md.0000000000012947
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D and bisphosphonates therapies for osteoporosis are associated with different risks of atrial fibrillation in women

Abstract: Osteoporosis and atrial fibrillation (AF) are common in post-menopausal women. Vitamin D and bisphosphonates are widely used to treat osteoporosis, and these may have different effects on the risk of AF.The goal of this study was to evaluate whether different agents for treating osteoporosis modulate the risk of AF in a population-based database.We identified 20,788 female patients suffering from osteoporosis who were or were not treated with vitamin D or bisphosphonates using the Taiwan National Health Insura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 31 publications
0
14
0
Order By: Relevance
“…21 An increased AF risk was also reported from a recently published observational study from Taiwan, which yet is not strictly comparable with our study, as BPs were compared to vitamin D rather than to other treatments, and the findings were based on small numbers. 22…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…21 An increased AF risk was also reported from a recently published observational study from Taiwan, which yet is not strictly comparable with our study, as BPs were compared to vitamin D rather than to other treatments, and the findings were based on small numbers. 22…”
Section: Discussionmentioning
confidence: 99%
“…When comparing results between studies, one must bear in mind the differences in the study populations. For example, the most recent observational study compared BP treatment versus vitamin D and none, rather than different active BP treatments 22 (Yang). Our cases and controls were part of a cohort of patients with pre-existing cardiovascular conditions, and this may lower external validity, that is, results may not be fully comparable with those reported by other researchers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…8,9) Studies evaluating the association between treatment with BPs and an increased risk of AF have yielded conflicting results, making the association between BPs with AF uncertain. [3][4][5]7,[10][11][12][13][14][15][16][17] Globally, AF is one of the most common clinical arrhythmias, especially in older persons. 18,19) The Framingham Heart Study reported that the prevalence of AF has increased by three-folds over the past 50 years.…”
Section: Introductionmentioning
confidence: 99%
“…1 Postmenopausal women are more likely than men to suffer from osteoporosis. 2 Risk factors for the disease include age, glucocorticoid use, and decreased bone mineral density (BMD). 3 The impairment of osteoblast differentiation and bone formation is also a cause of osteoporosis.…”
Section: Introductionmentioning
confidence: 99%